Clinical Impact of Antibiotics for the Treatment of Pseudomonas aeruginosa Biofilm Infections - Olivares, Elodie; Badel-Berchoux, Stéphanie; Provot, Christian; Prévost, Gilles; Bernardi, Thierry; Jehl, François (Frontiers in Microbiology, 2020)
Bacterial biofilms are highly recalcitrant to antibiotic therapies due to multiple tolerance mechanisms. The involvement of Pseudomonas aeruginosa in a wide range of biofilm-related infections often leads to treatment failures. Indeed, few current antimicrobial molecules are still effective on tolerant sessile cells. In contrast, increasingly studies showed that conventional antibiotics can, at low concentrations, induce a phenotype change in bacteria and consequently, the biofilm formation. Understanding the clinical effects of antimicrobials on the biofilm establishment is essential to avoid the use of inappropriate treatments in the case of biofilm infections. This article reviews the current knowledge about the bacterial growth within a biofilm and the preventive or inducer impact of standard antimicrobials on its formation by P. aeruginosa. The effect of antibiotics, used to treat biofilms of others bacterial species as Staphylococcus aureus or Escherichia coli, was also briefly mentioned. Finally, it describes two in vitro devices, which could potentially be used as antibiotic susceptibility testing for adherent bacteria.